Manning the margins: masculinity and writing in seventeenth-century France - Seifert, Lewis Carl (University of Michigan Press, 2009)
Civilizing the margins. The Chevalier de Méré's quest for honnête masculinity -- Effeminacy and its meanings from court to salon -- Vincent Voiture and the perils of galanterie -- Madeleine de Scudéry's tender masculinity -- Sexuality and the body at the margins. Writing sodomy: satire, secrets, and the "self" -- Border crossings: for a transgendered Choisy